Emozioni e sistema nervoso: la forza della musica e il ruolo della neurofisiologia (Materiali di Estetica. Terza serie, 2025)
Emotions are constantly present in our daily lives, arising from external stimuli or from our thoughts and influencing our behaviour. Involuntary responses are mediated by the autonomic nervous system, while most of our actions are controlled by cortical output that we are aware of. Emotions are somewhere in between, we are not always aware of them, but they strongly influence our actions. The deepest and oldest part of our brain is involved in the generation of emotions, connecting to all our organs and reaching the skin. Of the many emotions we can feel, anxiety is one of the most common and pervasive. It can negatively affect our cognitive performance, but music can powerfully modulate anxiety and many other emotions in both normal subjects and patients. Sympathetic skin response is a neurophysiological technique capable of detecting changes in skin impedande due to involuntary brief production of sweat as our autonomic nervous system follows emotions. This technique can demonstrate and measure the effect of music on our emotions.
Keywords: emotions; nervous system; sympathetic skin response; music